2020
DOI: 10.31584/jhsmr.2020738
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Illnesses and Student Academic Performance

Abstract: Innovations in healthcare have improved survival in children with illnesses previously considered fatal. Chronic illnesses in school-age children are increasing significantly, and these children are at higher risk for school problems than their healthy peers. To review the state of research on the impact of chronic illnesses on student academic performance, we reviewed original studies that investigated the relationship of child development, cognitive abilities, and academic achievement with common chronic ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Chronic illness has a negative impact on the physical, psychological, and academic performance of medical students. 32,33 The current study demonstrated that having chronic mental, neurological and other medical illnesses was correlated with a higher perception of stress and anxiety among the studied medical students.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Chronic illness has a negative impact on the physical, psychological, and academic performance of medical students. 32,33 The current study demonstrated that having chronic mental, neurological and other medical illnesses was correlated with a higher perception of stress and anxiety among the studied medical students.…”
Section: Discussionmentioning
confidence: 52%
“…The total score ranges from 0 to 56. Overall items were summed to determine the level of stress as follows: low level of stress ranged from (0-18), moderate level of stress (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), and high level of stress (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). 18 The validated Arabic version of PSS was used in the present study, 19 21 and is widely used to assess anxiety among students.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Lastly, the physical, mental and psychological elements of an individual are related to their quality of life [23]. However, poor habits and ways of life can lead to serious issues for an individual but not limited to obesity, diabetes, hypertension, anxiety and depression [24]. Chronic diseases would negatively impact the school performance of students.…”
Section: Problem Statementsmentioning
confidence: 99%
“…This non-adherence can manifest in heightened academic struggles, making learning and concentration more challenging, leading to potential academic underachievement (Hechtman et al, 2016; Wang et al, 2016). Moreover, behavioral issues can become more pronounced, complicating social interactions and possibly resulting in disciplinary actions at school or home (Barkley et al, 2004; Molina et al, 2009; Thongseiratch & Chandeying, 2020). There is an associated increased risk of developing co-morbid mental health disorders, further complicating the overall wellbeing of these children (Fischer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%